On the threshold of a new era: Private law versus robotics and artificial intelligence - Navas Tapia, Oswaldo (2021)
This essay addresses the conceptual themes that allow the magnitude of the emergence of AI, robotics and Big Data at the end of the second decade of the 21st century. It reviews the surprising goodness offered to man by intelligent technology that is intended to be autonomous and, for the same reason, poses ethical challenges that are not easy to address and less to solve. The Digital Age is removing, from its roots, the way we understand positive Law, as a power of imperium of the State, because the regulation of human activity, with unusual speed, is moving to private initiative. The UE has generated important regional regulations that could well serve as a guide for the rest of the world. Robotics, in particular, raises serious concern in the field of civil liability and in the world of work due to the potential elimination of sources of employment for human beings. KEYWORDS: Artificial intelligence, robotics, algorithm, active learning, legal system. JEL CODE: K0, K00